1972
DOI: 10.3133/ofr72160
|View full text |Cite
|
Sign up to set email alerts
|

Selected streamflow characteristics as related to channel geometry of perennial streams in Colorado

Abstract: The mean annual runoff and peak discharges having selected recurrence intervals have been related to the width and average depth of cross sections between channel and point bars for 53 gaged sites on perennial streams in the mountain region of Colorado. These relations and measures of channel dimensions can be used to estimate streamflow characteristics for ungaged streams in the Colorado mountain region. The standard error of estimate is 18.3 percent for the relation with mean annual runoff, and ranges from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…the discharge or range of discharges that transports the largest sediment load over a period of years and has the ability to shape the channel) since Wolman and Miller's (1960) and Wolman and Gerson's (1978) well-known publications on the magnitude, frequency and duration of geomorphic forces responsible for channel formation and recovery. Regionally specific empirical equations, describing relations among bankfull channel dimensions of width, depth and area and bankfull discharge are used extensively across the US for geomorphic assessments, stream rehabilitation and channel design (Hedman et al, 1974;Dunne and Leopold, 1978;Harman et al, 1999;Maner, 1999;Castro and Jackson, 2001). Bankfull discharge for many streams in the US has a recurrence interval of about 1.5 years, based on the annual mean daily streamflow series at rural USGS gages (Leopold et al, 1964;Dunne and Leopold, 1978;Andrews, 1980;Leopold, 1994;Rosgen, 1996;Castro and Jackson, 2001).…”
Section: Previous Applicationsmentioning
confidence: 99%
“…the discharge or range of discharges that transports the largest sediment load over a period of years and has the ability to shape the channel) since Wolman and Miller's (1960) and Wolman and Gerson's (1978) well-known publications on the magnitude, frequency and duration of geomorphic forces responsible for channel formation and recovery. Regionally specific empirical equations, describing relations among bankfull channel dimensions of width, depth and area and bankfull discharge are used extensively across the US for geomorphic assessments, stream rehabilitation and channel design (Hedman et al, 1974;Dunne and Leopold, 1978;Harman et al, 1999;Maner, 1999;Castro and Jackson, 2001). Bankfull discharge for many streams in the US has a recurrence interval of about 1.5 years, based on the annual mean daily streamflow series at rural USGS gages (Leopold et al, 1964;Dunne and Leopold, 1978;Andrews, 1980;Leopold, 1994;Rosgen, 1996;Castro and Jackson, 2001).…”
Section: Previous Applicationsmentioning
confidence: 99%
“…They showed that channel geometry-based estimates of 5-and 10-year return periods are often as reliable as those based upon 5-10 years of streamflow records. In the USA, the relationship between flood discharge and river channel dimensions was first developed following the suggestion of Langbein (1960) after research in Nevada; after a succession of studies, including Hedman et al (1972Hedman et al ( , 1974, Scott & Kunkler (1976), Riggs (1978), Osterkamp & Hedman (1979, 1982, Webber & Roberts (1981), Omang et al (1983), Wahl (1983Wahl ( , 1984 and Lawlor (2004), the method was accepted by the water resource division of the US Geological Survey as an operational technique. Considerable progress has been made in the USA in estimation of discharge from channel geometry for specific regions and is summarized by Wahl (1984).…”
Section: Flood Estimation From River Channel Dimensionmentioning
confidence: 99%
“…Progress in the estimation of flood discharges from river channel dimensions was first achieved in the USA following the suggestion of Langbein (1960) after research in Nevada; and after a succession of studies, including Hedman (1970), Hedman et al (1972Hedman et al ( , 1974, Scott & Kunkler (1976), Riggs (1978), Osterkamp & Hedman (1979, Webber & Roberts (1981), , Omang et al (1983a,b), and Wahl (1983Wahl ( , 1984, the method was accepted by the Water Resources Division of the US Geological Survey as an operational technique. Outside the USA, success has been reported for New Zealand (Mosley, 1979), northwest Italy (Caroni, 1982), Great Britain (Wharton et al, , 1995a and details of the derivation and application of equations for Java, Burundi, Ghana and Tanzania are presented for the first time in this paper.…”
Section: Flood Estimation From River Channel Dimensionsmentioning
confidence: 99%